Rhizobacteria of Bali With Obvious Growth-Promoting Properties on Corn (Zea mays L.) - Maulina, Ni Made Intan; Suprapta, Dewa Ngurah; Temaja, I Gede Rai Maya; Adnyana, I Made; Suriani, Ni Luh (Frontiers in Sustainable Food Systems, 2022)
Corn productivity in Indonesia is still relatively low compared with other countries. Therefore, it is necessary to increase the productivity of corn by using rhizobacteria, which have multiple traits. This study was conducted to obtain indigenous rhizobacteria of Bali that have multiple traits, can produce indoleacetic acid (IAA), fix nitrogen from atmosphere, produce siderophores, colonize roots, increase seed germination, and promote the growth of corn. Isolation of rhizobacteria was carried out from the rhizosphere of plants belonging to the Gramineae family that grows in Bali Island, Indonesia. Six isolates, namely, Sr3, Tb9, Rg1, Rg23, Al27, and Jg8, could produce IAA, fix nitrogen from the atmosphere, produce siderophores, and increased germination rate and vigor index of corn seedling. Among them, three isolates, namely, Rg1, Sr3, and Jg8, significantly (p <0.05) increased the germination rate of corn seeds, increased vigor index, increased root dry weight and shoot dry weight of corn at the age of 7 days, and were able to colonize corn roots. Compared with the control, the rhizobacteria treatment increased the germination of corn seeds ranging from 5.04 to 13.05%. Based on the analysis of the 16S rRNA gene, it was found that these rhizobacteria species were Glutamicibacter nicotianae strain Rg1 (accession number OM349119), Brevibacillus invocatus strain Sr3 (accession number OM327515), and Micrococcus luteus strain Jg8 (accession number OM362349). Under a greenhouse condition, all the three isolates significantly (p <0.05) increased nutrient uptake, the leaf chlorophyll content, net assimilation rate, and crop growth rate of corn when compared with control. These results suggested that these isolates of rhizobacteria obviously promoted the growth of corn and can be developed as biostimulant to promote the growth and increase the corn yield in Bali, Indonesia.